2015
DOI: 10.1021/acs.jpcb.5b06525
|View full text |Cite
|
Sign up to set email alerts
|

Solvation Thermodynamic Properties of Hydrogen Sulfide in [C4mim][PF6], [C4mim][BF4], and [C4mim][Cl] Ionic Liquids, Determined by Molecular Simulations

Abstract: Removal of hydrogen sulfide (H2S) and acid gases from natural gas is accomplished by absorption processes using a solvent. The gas solubility in a liquid can be used to measure the degree of removal of the gas and is quantified by the Henry's constant, the free energy of solvation at infinite dilution, or the excess chemical potential. In this work, Henry's constants and thermodynamic properties of solvation of H2S were calculated in three ionic liquids: [C4mim][PF6], [C4mim][BF4], and [C4mim][Cl] ([C4mim], 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 95 publications
1
12
0
Order By: Relevance
“…With the aid of molecular simulations, deeper insights can be gained about the entropic and enthalpic contributions of H 2 S solubilities in different ILs. Recently, Sánchez-Badillo and co-workers computed solvation thermodynamics of H 2 S in ILs and demonstrated qualitative agreement with experimental data . These calculations showed that, at room temperature, the absolute solvation enthalpy is 2 times higher than the absolute entropic contribution for [bmim + ]­[PF 6 – ] and [bmim + ]­[BF 4 – ] and 3 times higher for [bmim + ]­[Cl – ].…”
Section: Absorptionmentioning
confidence: 99%
“…With the aid of molecular simulations, deeper insights can be gained about the entropic and enthalpic contributions of H 2 S solubilities in different ILs. Recently, Sánchez-Badillo and co-workers computed solvation thermodynamics of H 2 S in ILs and demonstrated qualitative agreement with experimental data . These calculations showed that, at room temperature, the absolute solvation enthalpy is 2 times higher than the absolute entropic contribution for [bmim + ]­[PF 6 – ] and [bmim + ]­[BF 4 – ] and 3 times higher for [bmim + ]­[Cl – ].…”
Section: Absorptionmentioning
confidence: 99%
“…43 In this work, the excess chemical potential of thiophene in a series of imidazolium-based ILs was calculated using classical MD simulations. The ILs studied were selected based on toxicity effects, 27,[44][45][46] 24,47,48 due to its low viscosity 49 and large commercial availability 50 compared with other ILs. Previous experimental and electronic structure calculations reported in the literature, suggested that the extraction of aromatic sulfur compounds in ILs, is related to p-stacking interactions between rings and sulfur-hydrogen interactions with the cation's alkyl chain.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the low heat capacity of ILs (normally lower than 2 J·g −1 ·K −1 ) can potentially reduce the energy consumption of desorption process . A number of literature have reported the solubilities of H 2 S and CO 2 in various normal ILs as physical absorbents, showing that the Henry's law constants of H 2 S in normal ILs are generally in the range of 2∼4 MPa and the ideal selectivities of H 2 S/CO 2 are generally in the range of 2∼4 …”
Section: Introductionmentioning
confidence: 99%